2021
DOI: 10.1016/j.buildenv.2020.107368
|View full text |Cite
|
Sign up to set email alerts
|

Review and comparison of HVAC operation guidelines in different countries during the COVID-19 pandemic

Abstract: Various organizations and societies around the globe have issued guidelines in response to the coronavirus disease (COVID-19) and virus (SARS-CoV-2). In this paper, heating, ventilating, and air-conditioning-related guidelines or documents in several major countries and regions have been reviewed and compared, including those issued by the American Society of Heating Refrigerating and Air-Conditioning Engineers, the Federation of European Heating, Ventilation, and Air Conditioning Associations, the Society of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
157
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 18 publications
1
157
0
2
Order By: Relevance
“…The main results are provided in Table 1. Of all identified studies, 10 were experimental research on HVAC systems and COVID spread (Chen and Zhao, 2020;Chirico et al, 2020;Coccia, 2020;Correia et al, 2020b;Guo et al, 2020;Haque and Rahman, 2020;Mousavi and Grosskopf, 2015;Qian and Zheng, 2018;Rosario et al, 2020;Shajahan et al, 2019). These articles were from China (2), the USA (1), Japan (1), Italy (2), Bangladesh (1), Portugal (1), Indonesia (1), and Brazil (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main results are provided in Table 1. Of all identified studies, 10 were experimental research on HVAC systems and COVID spread (Chen and Zhao, 2020;Chirico et al, 2020;Coccia, 2020;Correia et al, 2020b;Guo et al, 2020;Haque and Rahman, 2020;Mousavi and Grosskopf, 2015;Qian and Zheng, 2018;Rosario et al, 2020;Shajahan et al, 2019). These articles were from China (2), the USA (1), Japan (1), Italy (2), Bangladesh (1), Portugal (1), Indonesia (1), and Brazil (1).…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles were observational and had investigated the association between Eight of the 20 included studies on poor ventilation, effective ventilation, and key elements of ventilation to prevent COVID-19. There are many studies about temperature and humidity, reporting that humidity should range from 40 to 60% and temperature should be 21-23 • C (Guo et al, 2020). However, low RH (<20%) is known to increase an individual's susceptibility to infection (Dietz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…6-7), therefore, there is the lowest risk of infectious diseases such as coronavirus in scenario 4. Guo et al found that effective airflow patterns are the most important infectious disease control strategy by air diluting the around the infectious agent's sources (Guo, Xu et al 2020). Hence, it is recommended that occupants seat near the air supply or locate the air supply close to the breathing zone because using ventilation can reduce the risk of infectious aerosols.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical ventilation systems are implemented in the residential home for thermal comfort and to regulate indoor air distribution(Babu and Suthar 2020). During an epidemic, such as the COVID-19 pandemic, air recirculation should be avoided, and the system operated on 100% outdoor air if possible (Joppolo and Romano 2017;Guo, Xu et al 2020). But, there is a limitation in the use of the outdoor air in the autumn and winter seasons.…”
Section: Introductionmentioning
confidence: 99%
“… 30 In a lot of regions, indoor dining is still going on. Although various measures have been proposed 31–34 for maintaining a clean indoor environment, most measures do not consider the transmission characteristics of the airborne droplets and aerosols. The detailed information on the movement, trajectories, and deposition of the droplets is useful in making guidelines that prevent people from infection during indoor activities.…”
Section: Introductionmentioning
confidence: 99%